Cavanaugh stakeout - Ferrarella, Marie (Ferrarella, Marie. Cavanaugh justice., 2019)
"When a civilian disappears, Detective Finn Cavanaugh catches the case. His partner-in-catching-crime? Brainy and beautiful insurance investigator Nik Kowalski, whose method of pursuing people clashes with Finn's own--and whose charms prove all too alluring. As their missing-person case heats up, Nik and Finn race to find the killer haunting their waking nightmares."--Back cover.